Measuring the CP property of Higgs coupling to tau leptons in the VBF channel at the LHC - Tao Han (Journal of High Energy Physics, 2017)
Abstract We study the prospects of measuring the CP property of the Higgs (h) coupling to tau leptons using the vector boson fusion (VBF) production mode at the high-luminosity LHC. Utilizing the previously proposed angle between the planes spanned by the momentum vectors of the (π + π 0) and (π − π 0) pairs originating in τ ± decays as the CP-odd observable, we perform a detailed Monte Carlo analysis, taking into account the relevant standard model backgrounds, as well as detector resolution effects. We find that excluding a pure C O 400 f b − 1 $$ \mathcal{O}\left(400\ {fb}^{-1}\right) $$ luminosity at the 14 TeV LHC, and values of the CP-mixing angle larger than about 25° can be excluded at 95% confidence level using 3 ab−1 data. It is observed that the uncertainty in the angular resolution of the neutral pion momenta does not constitute a significant hurdle. Achieving a signal to background ratio (S/B) close to one, while keeping a high enough signal yield required to study the angular distributions selects out VBF as a promising mode to probe the CP nature of the hτ τ coupling, with gluon fusion suffering from a low S/B, and the W ± h/Zh mode (with leptonically decaying W ± /Z) having a much smaller signal rate.